DEVELOPMENT OF FLASHCARD MEDIA BASED ON BLENDED LEARNING FOR PRIMARY SCHOOL TEACHER EDUCATION (PGSD) STUDENTS AT KHAIRUN TERNATE UNIVERSITY - Iwan Abdy; Lis Susilawati (UIBU, 2023)
Education is an aspect of life that is closely related to human life, and education is one of the pillars that plays an important role in creating quality people. This study is based on a lack of student understanding of the use of interesting media in the learning process. The purpose of this study is to develop and test the feasibility and effectiveness of a 'flashcard-based blended learning' media. The type of research is research and development using the ADDIE model. Research methods are analysis, design, development, implementation and evaluation. The subjects were 30 PGSD fifth semester students. Observations, tests, interviews, questionnaires, and documents are used to collect records. Data analysis techniques using product data analysis, initial data analysis, hypothesis testing, and n-gain testing. The results showed that the media